Dampak Sumber Daya VRIN terhadap Keunggulan Bersaing dan Kinerja (Studi pada UKM di Medan) - Miraza, Zuwina; Hafas, Hafriz Rifki (Jurnal Manajemen dan Organisasi, 2015)
In order to achieve positive performance growth in this era of global competition, Small Medium Enterprises (SMEs) must have sustainable competitive advantages. Competitive advantages can be obtainedif SME have Valuable, Rare, Inimitable and Non-substitutable (VRIN) resources. Therefore this research aimed to study the effects of VRIN resources to competitive advantages and performance. The subjects of this study was 187 SMEs listed in Cooperation Office and SME of Medan. Using path analysis, the obtained result shows that rareness gave direct effects to performance and in-immitable gave indirect effects to performance through competitive advantages as intervening.Keywords: VRIN, competitive advantage, performance, small medium enterprises